Percepcja ryzyka niepowodzenia zawodowego wśród studentów - Wódz, Jacek; Szczepańska-Woszczyna, Katarzyna (Studia Edukacyjne, 2018)
The author reflects on the risk of professional failure among students. He believes that in this case we have a vague definition of professional failure. He indicates both causes, those independent of humans and those related to their own actions or negligence. Then he refers to the category of occupation and its place in times of uncertainty. Pointing to the factors determining the perception of the risk of professional failure, he emphasizes the role of the University, which gives support to its students in the process of their professional risk assessment.